Особливості творення та вживання абревіатур медичної термінології в англомовних історіях хвороб - Соляненко, Олена Леонідівна; Solianenko, O. L. (My University, 2017)
У статті проаналізовано творення та вживання різних видів абревіатур (скорочень) в англомовних історіях хвороб. Акцентовано увагу на існуванні різних поглядів лінгвістів на класифікацію та особливості творення скорочень лексичних одиниць медичної англомовної термінології. Розглянуто варіанти вживання можливих абревіатур медичних термінів, які використовуються при описі хвороб травної, нервової, серцево-судинної та дихальної систем. The article deals with various types of abbreviation usage in English medical case reports. The meticulous attention is paid to linguists’ different view points on classification and reducing lexical units in medical terminology. The features of lexical and graphic medical abbreviations in English are highlighted. The phenomenon of abbreviation as a clipping (creation by shortening) and its types (apocope, apheresis, syncope and their word-forming combinations) is considered. The relevant examples of these reductions from English medical case reports are given. Some examples concerning Latin borrowing medical abbreviations are dealt with. Different types of graphic abbreviations for the same medical term are presented. Some variants of possible abbreviations of medical terms used in describing diseases of the gastrointestinal, nervous, cardiovascular and respiratory systems are explored.
Formation and Usage Features of Medical Terminology Abbreviations in English Case Reports
Keywords: абревіатура; медична термінологія; скорочення англійських медичних термінів; англомовні історії хвороб; особливості вживання англійських медичних термінів; abbreviation; medical terminology; reduction of English medical terms; English medical case reports; peculiarities of using English medical terms